Competitiveness to Support the National Defense System - Setia, Adang; Purwowidagdo, Sapto J. (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2015)
The purpose of this research is to identified competitiveness Indonesian Aerospace Inc. (IAe) to support the national defense system. This research is a descriptive with qualitative interview as method and using the theory of reference are: (1) Five Forces Porter; (2) Design School Mintzberg; (3) Core Competence and Resource base strategy. IAe is currently on the process of organizational transformation, the finding also suggest competitiveness can be said to be low. But there is a potential factor that causes IAe competitive advantage in the industry to improve the future development IAe and contribute to the realization of the national defense system.